A co-culture microtunnel technique demonstrating a significant contribution of unmyelinated Schwann cells to the acceleration of axonal conduction in Schwann cell-regulated peripheral nerve development. Issue 8 (5th June 2017) - Sakai, Koji; Shimba, Kenta; Kotani, Kiyoshi; Jimbo, Yasuhiko
Abstract : The authors developed a co-culture technique inside a microtunnel and demonstrated that Schwann cells increase axonal conduction velocity before myelination. Abstract : Schwann cells (SCs) contribute to the regulation of axonal conduction in a myelin-dependent and -independent manner. However, due to the lack of investigative techniques that are able to record axonal conduction under conditions that control the proliferation of specific SC types, little is known about the extent to which myelinated SCs (mSCs) and unmyelinated SCs (umSCs) modulate axonal conduction. In this study, a microtunnel–electrode approach was applied to a neuron/SC co-culture technique. Rat dorsal root ganglion neurons and SCs were co-cultured in a microtunnel–electrode device, which enabled recording of the conduction delay in multiple axons passing through microtunnels. Despite the absence of nuclei in the microtunnel when SCs were eliminated, cultured cells were densely packed and expressed S100 beta (an SC marker) at a rate of 96% in neuron/SC co-culture, indicating that SCs migrated into the microtunnel. In addition, supplementation with ascorbic acid after 6 days in vitro (DIV) successfully induced myelination from 22 DIV. Activity recording experiments indicated that the conduction delay decreased with culture length from 17 DIV in the neuron/SC co-culture but not in neuron monoculture. Interestingly, the SC-modulated shortening of conduction delay was attenuated at 17 DIV and 22 DIV by supplementing the culture medium with ascorbic acid and, at the same time, suppressing SC proliferation, suggesting that immature umSCs increased axonal conduction velocity in a cell density-dependent manner before the onset of myelination. These results suggest that this method is an effective tool for investigating the contributions of mSCs or umSCs to the regulation of axonal conduction.